Systematic Literature Review: Pendidikan Matematika Realistik Berbasis Etnomatematika - Faiza Izzati Mufti; Meiliasari; Wardani Rahayu (Jurnal Riset Pendidikan Matematika Jakarta, 2025)
With the problem of having difficulty understanding mathematical ideas experienced by students, due to the abstract nature of ideas and their rarity in our everyday existence. Therefore, the need arises for a Realistic Mathematics Education (PMR) method that offers learning from an authentic setting. This research aims to conduct a literature review related to Realistic Mathematics Education (PMR) and the effectiveness of the ethnomathematics-based Realistic Mathematics Education approach. Systematic Literature Review (SLR) is the research method chosen for this research. The data collection process includes collecting and analyzing every publication published between 2007 and 2023 that discusses ethnomathematics-based realistic mathematics education. The journals used in this research were 15 national and international journals indexed by SINTA and SCOPUS. Research findings show that PMR techniques build mathematical concepts by utilizing real-world contexts. Everyday existence occurs within a cultural framework. Learning with an ethnomathematics-based PMR approach is effective to use because it can improve various types of mathematical abilities.